A longitudinal cohort study on quality of life in stroke patients and their partners: Restore4Stroke Cohort. Issue 1 (13th September 2012) - van, Maria L.; van, Caroline M.; Post, Marcel W. M.; Lindeman, Eline; de, Paul L. M.; Visser‐Meily, Johanna M.A.
<x xml:space="preserve">Abstract</x> Background Stroke is a major cause of disability in the Western world. Its long‐term consequences have a negative impact on the quality of life of both the patients and their partners. Aim The aim of the Restore4Stroke Cohort study is to investigate the changes in quality of life of stroke patients and their partners over time, and to determine factors predicting quality of life in several domains, especially personal and environmental factors. Method Multicentre prospective longitudinal cohort study. Inclusion and the first assessment take place during hospital stay in the first week post‐stroke. Follow‐up assessments take place at two months, six months, one year, and two years post‐stroke. Recruitment of 500 patients from stroke units in six participation hospitals is foreseen. If the patient has a partner, he or she is also asked to participate in the study. Outcomes The main outcome is quality of life, considered from a health‐related quality of life and domain‐specific quality of life perspective. Factors predicting long‐term quality of life will be determined by taking into account the health condition (pre‐stroke health condition and stroke‐related health condition), personal factors (e.g. coping and illness cognitions), and environmental factors (e.g. caregiver burden and social support). Discussion This study is expected to provide information about the changes in quality of life of stroke patients and their partners over time. Furthermore, the identification of factors predicting quality of life can be used to improve rehabilitation care and develop new interventions for stroke patients and their partners.